Service Delivery and Decentralization in Sri Lanka : Assessment and Options - World Bank (Washington, DC, 2014)
This report assesses Sri Lanka's experience with decentralization to date and discusses options for decentralization and implications for service delivery in three sectors: roads, solid waste and health. The selected sectors illustrate the considerations relevant to the decentralization decision and its future direction. The services selected cover a range of central, provincial and local responsibilities in delivery and illustrate how the cause of success or failure of service delivery is rooted in the institutional framework, division of responsibility, funding mechanisms i.e. incentives and accountability. The effective provision of these services requires a clear understanding of the service delivery goals, technical capacity, adequate assets and recurrent inputs to deliver services. Each sector has its particular needs and to some extent can be considered independently, but the political realities effectively require that any constitutionally mandated and elected level of government have some corresponding responsibilities.